Determinasi Kinerja Karyawan: Komunikasi, Technology Acceptance dan Pengambilan Keputusan (Literature Review Executive Support Sistem For Business) - Sri Wahono; Hapzi Ali (Jurnal Ekonomi Manajemen Sistem Informasi, 2023)
With effective communication, achieving company goals will be easier to do, from this effective communication information can be obtained that can make data in decision making. Technology acceptance which functions to explain and predict user acceptance of an information system. Technology Acceptance provides a theoretical basis for analyzing between beliefs and behavior, from the actual use of users of an information system. Meanwhile, the information obtained from communication and technology acceptance will become data for making rational decision-making, so that it really supports the decision-making process that is right on target. Utilization of acceptance technology and effective communication and decision-making management have a role in improving employee performance. The role of the three variables in a company is important because it will assist management in the process of improving employee performance.